2012
DOI: 10.1007/s00360-012-0688-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative meta-analysis of maximal aerobic metabolism of vertebrates: implications for respiratory and cardiovascular limits to gas exchange

Abstract: Maximal aerobic metabolic rates (MMR) in vertebrates are supported by increased conductive and diffusive fluxes of O(2) from the environment to the mitochondria necessitating concomitant increases in CO(2) efflux. A question that has received much attention has been which step, respiratory or cardiovascular, provides the principal rate limitation to gas flux at MMR? Limitation analyses have principally focused on O(2) fluxes, though the excess capacity of the lung for O(2) ventilation and diffusion remains une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 66 publications
3
49
0
Order By: Relevance
“…The concept of symmorphosis (Weibel et al, 1991;Weibel, 2000) suggested there was no rate-limiting step to maximal O 2 transport because it was assumed that natural selection would eliminate excess capacity in a complex pathway such as O 2 transport (Weibel et al, 1991). The problem with the symmorphosis concept as applied to rate-limitation analysis is that is focuses solely on O 2 and ignores the role that these same transport processes play in eliminating CO 2 produced by the mitochondria (see Hillman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of symmorphosis (Weibel et al, 1991;Weibel, 2000) suggested there was no rate-limiting step to maximal O 2 transport because it was assumed that natural selection would eliminate excess capacity in a complex pathway such as O 2 transport (Weibel et al, 1991). The problem with the symmorphosis concept as applied to rate-limitation analysis is that is focuses solely on O 2 and ignores the role that these same transport processes play in eliminating CO 2 produced by the mitochondria (see Hillman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is perhaps no coincidence that species with thicker respiratory barriers (e.g., salamanders, lungfish, and tortoises) also tend to have larger cells (77). Passive diffusion may be just one of many colimiting steps on oxygen consumption (78).…”
Section: Discussionmentioning
confidence: 99%
“…As with birds and mammals, increased RMR gives rise to elevated body temperatures which, in turn, enhances energy turnover rates and aerobic performance (Clarke and Pörtner 2010). Even though the cost of transport for swimming animals is low compared to those that walk or fly (Schmidt-Nielsen 1972), which probably explains why many fish species exhibit a broad range of aerobically supported locomotory speeds with a relatively low MMR (Bennett and Ruben 1979;Hillman et al 2013), it appears that in temperate waters there is also strong selection on the capacity for remaining active.…”
Section: Selection For Increased Locomotor Capacitymentioning
confidence: 99%